Pengaruh strategi promosi media sosial untuk meningkatkan keputusan pembelian mahasiswa pada kedai kopi di banjarmasin - Rahmatul Jannatin Naimah; Redho Muhammad (BIMA: Jurnal Bisnis dan Manajemen, 2022)
The coffee shop business is growing rapidly in almost all major cities in Indonesia, and Banjarmasin is no exception. The number of coffee shops in Banjarmasin ultimately creates increasingly fierce competition between shops to get visitors or consumers. This study aims to determine whether promotion using social media has an effect on consumer purchasing decisions at Banjarmasin coffee shops. The research uses a quantitative approach. The data collection technique used is a questionnaire. The number of samples taken was as many as 100 people. And the coffee shop that is used as the object of research is the Kawai Coffee Shop in Banjarmasin. The results of a simple linear regression analysis state that there is a relationship between social media promotion and purchase decisions. The findings show that there are 2 groups of respondents in which in the Social Media Promotion 1 (PMS 1) group, social media promotion has a significant positive effect on consumer purchasing decisions, while the Social Media Promotion 2 (PMS 2) group has no significant effect on social media promotion decisions. consumer purchases